2000
DOI: 10.1002/1099-1395(200101)14:1<25::aid-poc332>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase structural (internal) effects in strong organic nitrogen bases

Abstract: Gas‐phase basicities (GB) of strong organic bases containing the imino group were re‐examined in the light of the re‐evaluated GB values for the reference bases given in a recent compilation of Hunter and Lias. Structural (internal) effects which influence the basicity are discussed and general relations for the GB prediction are proposed for simple alkyl amidines and guanidines. These relations were used for estimation of cyclization and intramolecular H‐bonding effects. Copyright © 2000 John Wiley & Sons, Lt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
164
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(171 citation statements)
references
References 34 publications
7
164
0
Order By: Relevance
“…It is well known that the unusually high basicity of proton sponges is significantly influenced by the formation of intramolecular hydrogen bonds [13]. The tendency of diamines and diols to form IMHBs has been recognized for quite some time [14][15][16][17][18], but only recently, several papers of Raczynska et al [19][20][21][22][23], Koppel and coworkers [24] and theoretical investigations of Maksić and coworkers [25][26][27] have shown that the existence of flexible intramolecular hydrogen bonds plays a significant role in the tailoring of organic superbases. A representative example is provided by a guanidine bearing three 3-(N,N-dimethylamino)propyl groups, for which a gas-phase basicity comparable to those of phosphazenes has been predicted [28].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the unusually high basicity of proton sponges is significantly influenced by the formation of intramolecular hydrogen bonds [13]. The tendency of diamines and diols to form IMHBs has been recognized for quite some time [14][15][16][17][18], but only recently, several papers of Raczynska et al [19][20][21][22][23], Koppel and coworkers [24] and theoretical investigations of Maksić and coworkers [25][26][27] have shown that the existence of flexible intramolecular hydrogen bonds plays a significant role in the tailoring of organic superbases. A representative example is provided by a guanidine bearing three 3-(N,N-dimethylamino)propyl groups, for which a gas-phase basicity comparable to those of phosphazenes has been predicted [28].…”
Section: Introductionmentioning
confidence: 99%
“…Gas phase basicities of a number of guanidine derivatives with PAs larger than 239 kcal mol À1 (1000 kJ mol À1 ) have been experimentally evaluated by Raczynska et al [53,54]; the results are summarized in Table 2.10. Some trends for various classes of compounds could be identified.…”
Section: Guanidinesmentioning
confidence: 99%
“…6 Gas phase basicities of amidine derivatives[53,54] VIN ¼ vinamidine, FAM ¼ formamidine, AAM ¼ acetamidine, AM ¼ amidine, BAM ¼ benzamidine, EAM ¼ Et 2 Nacetamidine; CAM ¼ cyclic amidine.d Re-evaluated values with different reference base. e B3LYP/6-31G* gas phase value[55].…”
mentioning
confidence: 99%
“…In addition, rotational isomerism for the ethylamino side chain in both ligands and prototropic tautomerism of the imidazole ring in histamine (HA1 and HA2 tautomers) were considered for each type of adducts. To reduce the cost of calculations, the initial structures for adducts have been obtained by a replacement of the proton by the lithium cation Li + in the previously observed monocationic structures of HA and AEP [12][13][14][15][16][17]. In this way, 22 thermodynamically stable structures were obtained for the lithium cation-histamine adduct (Fig.…”
Section: Possible Conformations Of Isolated Ha-li + and Aep-li + Adductsmentioning
confidence: 99%
“…In previous papers, our attention was mainly concentrated on the proton-transfer reactions for histamine and its agonist 2-(␤-aminoethyl)-pyridine [12][13][14][15][16][17]. It has been found that similarly to other bidentate nitrogen ligands with a flexible conformation (diamines, aminoamidines, aminoguanidines), HA and AEP exhibit exceptionally high basicity in the gas-phase.…”
Section: Introductionmentioning
confidence: 99%